P–655 Modelling patient selection in fresh vs. frozen-thawed IVF cycles in poor prognosis patients. (6th August 2021) - Patrizio, P; Molinari, E; Albertini, D F; Darmon, S K; Barad, D H; Gleicher, N
Abstract: Study question: What is in poor-prognosis patients the impact of patient selection on outcome comparisons between fresh and frozen-thawed in vitro fertilization (IVF) cycles? Summary answer: In poor prognosis patients, all-freeze cycles offer no outcome benefits and may, indeed, adversely affect IVF outcomes. What is known already: Some in primarily good prognosis patients performed studies have suggested improved IVF outcomes if in stimulated cycles all embryos are cryopreserved (all-freeze cycles) and, after a time interval, in a later thaw cycle transferred. All-freeze cycles, therefore, despite considerable criticism, have become increasingly popular. Study design, size, duration: Retrospective controlled cohort study involving 4 different patient pairings of 1st IVF cycles at our center between 2017–2020. Participants/materials, setting, methods: n an academically affiliated private fertility and research center, we compared: (i) 127 fresh vs. 193 frozen donor recipient cycles; (ii) 741 fresh autologous vs. 217 frozen autologous cycles; (iii) 143 favorably selected autologous vs. same 217 frozen autologous cycles; and (iv) 598 poorer prognosis autologous vs. same 217 frozen autologous cycles. Main outcome measures were standard IVF outcomes. Main results and the role of chance: Even in poor prognosis patients, patient selection to significant degrees impacts how fresh and frozen-thawed IVF cycles compare. Though the concept of embryo freezing with delayed embryo transfer may to a marginal degree beneficially affect IVF outcomes in best-prognosis patients, in unselected patients it has no effect on outcomes, while in poor-prognosis patients it adversely affects IVF outcomes. Unexpectedly, we also discovered a substantial impact of recipient age in donor-egg cycles on IVF outcomes because of age-associated increases in miscarriage rates independent of embryo aneuploidy. Limitations, reasons for caution: Like in all retrospective studies, unknown patient selection biases cannot be ruled out. Moreover, because of the highly atypical characteristics of our center's patient population, generalization of here reported outcomes to more typical IVF patient populations must be viewed with caution. Wider implications of the findings: In poor-prognosis patient, all-freeze IVF cycles should be avoided and considered contraindicated since they reduce outcomes. Since only best-prognosis patients benefit, with intermediate-prognosis, the practice should also be avoided. Unexpectedly, this study for the first time also revealed in recipients increasing miscarriages with advancing age (obviously not chromosomal). Trial registration number: NA